2019
DOI: 10.1002/hep.30871
|View full text |Cite
|
Sign up to set email alerts
|

Peribiliary Gland Niche Participates in Biliary Tree Regeneration in Mouse and in Human Primary Sclerosing Cholangitis

Abstract: Background and Aims Mechanisms underlying the repair of extrahepatic biliary tree (EHBT) after injury have been scarcely explored. The aims of this study were to evaluate, by using a lineage tracing approach, the contribution of peribiliary gland (PBG) niche in the regeneration of EHBT after damage and to evaluate, in vivo and in vitro, the signaling pathways involved. Approach and Results Bile duct injury was induced by the administration of 3,5‐diethoxycarbonyl‐1,4‐dihydrocollidine (DDC) diet for 14 days to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…On the other hand, frequently used markers to identify DRCs, such as epithelial cell adhesion molecule, SOX9, and cytokeratins 7 and 19, lack specificity as they are not exclusively expressed by DRCs but also by normal cholangiocytes and, in some cases, SCs. Nevertheless, recent lineage‐tracing studies have demonstrated that DRCs in biliary injury are mainly derived from the expansion of proliferative cholangiocytes (particularly of a select population with persistent proliferative activity) and/or activation of biliary tree progenitor/stem cells in the peribiliary gland niche . This etiology‐dependent origin of DRCs likely affects their interaction with nonparenchymal cells within the ductular reaction, as demonstrated by a recent study that compared the transcriptomic profile of DRCs/HPCs from hepatitis C virus–infected and PSC livers as models for hepatocellular or biliary injury, respectively.…”
Section: The Proliferative Cholangiocyte Compartment In Psc: Drcsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, frequently used markers to identify DRCs, such as epithelial cell adhesion molecule, SOX9, and cytokeratins 7 and 19, lack specificity as they are not exclusively expressed by DRCs but also by normal cholangiocytes and, in some cases, SCs. Nevertheless, recent lineage‐tracing studies have demonstrated that DRCs in biliary injury are mainly derived from the expansion of proliferative cholangiocytes (particularly of a select population with persistent proliferative activity) and/or activation of biliary tree progenitor/stem cells in the peribiliary gland niche . This etiology‐dependent origin of DRCs likely affects their interaction with nonparenchymal cells within the ductular reaction, as demonstrated by a recent study that compared the transcriptomic profile of DRCs/HPCs from hepatitis C virus–infected and PSC livers as models for hepatocellular or biliary injury, respectively.…”
Section: The Proliferative Cholangiocyte Compartment In Psc: Drcsmentioning
confidence: 99%
“…Nevertheless, recent lineage-tracing studies have demonstrated that DRCs in biliary injury are mainly derived from the expansion of proliferative cholangiocytes (particularly of a select population with persistent proliferative activity) and/or activation of biliary tree progenitor/ stem cells in the peribiliary gland niche. (13,16,17) This etiology-dependent origin of DRCs likely affects their interaction with nonparenchymal cells within the ductular reaction, as demonstrated by a recent study that compared the transcriptomic profile of DRCs/HPCs from hepatitis C virus-infected and PSC livers as models for hepatocellular or biliary injury, respectively. The study identified significant differences in the expression of over 300 genes between the DRCs of the two diseases and defined how these differences influence the recruiting and homing of inflammatory cells.…”
Section: The Proliferative Cholangiocyte Compartment In Psc: Drcsmentioning
confidence: 99%
“…Altogether, these findings are confirmed by single-cell transcriptomic analysis in human, with the identification of an EpCAM pos / TROP2 int / MUC6 high progenitor compartment with prominent stem cell features ( 9 ). Moreover, the contribution of PBG cells in the regeneration of mature biliary epithelium has been demonstrated in experimental conditions and by an ex vivo human model of biliary regeneration, which have disclosed that PBG cells can repopulate the surface epithelium of bile ducts by proliferation and differentiation into mature cholangiocytes ( 25 , 28 , 29 ).…”
Section: The Heterogeneity Of Epcam Pos Cell Populmentioning
confidence: 99%
“…PBGs are tubulo-alveolar mucous glands, in continuity with the surface epithelium of the bile duct ( 22 , 23 ). Intriguingly, the EpCAM pos cell population within PBGs showed stem/progenitor properties, including organoid formation and plasticity to differentiate into hepatocytes, cholangiocytes, and endocrine pancreatic cells ( Figure 2 , panel B) ( 21 , 24 , 25 ). PBG cells have been collectively named biliary tree stem/progenitor cells (BTSC) and, embryologically, they represent the remnant of the common bilio-pancreatic progenitors of the ventral endoderm ( 23 , 24 ).…”
Section: The Heterogeneity Of Epcam Pos Cell Populmentioning
confidence: 99%
See 1 more Smart Citation